The effects of individual judgments about selection procedures: Results from a power-to-resist game - Vanessa Mertins; Henrik Egbert; Tanja Könen (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2011)
We use a power-to-resist game to find out the effects of individuals' judgments about a proposer's selection procedure on the willingness to offer resistance against proposed outcomes. In the experiment, one individual is selected on the grounds of a particular procedure. This individual is allowed to propose how to allocate a pie among five group members: herself and four responders. After that each responder in the group can decide whether to offer costly resistance against the proposed allocation. Resistance is modeled as a threshold public good. If resistance is successful, the proposer receives nothing. If resistance is unsuccessful, the pie is distributed according to the proposer's decision. We find that resistance increases with (a) the size of the proposal, with (b) subjectively perceived unfairness of the selection procedure of the proposer's role, and with (c) the individual procedural preferences being unsatisfied. Surprisingly, resistance is not affected by the fact whether or not the group's majority vote on the selection procedure is respected. We check for robustness of our results and find that results are stable over two countries. The presented evidence suggests that procedural effects over and above outcomes are relevant in strategic interaction.
Keywords: C91; D23; D63; D72; H41; O57; 330; selection procedure; favored process effect; fair process effect; procedural fairness; legitimacy